Manfaat Preventif Ginkgo Biloba dalam Kedokteran : Tinjauan Sistematik - Agung Wijayanto; Fahmi Nofriandi; M. Syaoqi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
This systematic literature review (SLR) aims to evaluate the preventive benefits of Ginkgo Biloba in the fields of pulmonary health, cardiovascular health, and forensic medicine. The analysis includes randomized controlled trials (RCTs), in vivo experimental studies, and relevant literature reviews from the past five years. This study follows PRISMA guidelines to assess the effectiveness of Ginkgo Biloba in addressing respiratory disorders, enhancing cardiovascular function, and supporting forensic medicine, particularly in toxicity management and cognitive recovery. Based on the search results, 12 articles that met the inclusion criteria were selected for further analysis, providing evidence of the positive potential of Ginkgo Biloba across these three areas.